The Cartel Party and the Rise of the New Extreme Right - PELIZZO, Riccardo (Institutional Knowledge at Singapore Management University, 2007)
In the cartel party literature, there are three different arguments as to why the behavior of Western European parties resembles the behavior of oligopolistic firms. Each version of the cartel party hypothesis hypothesized that the rise of the parties of the new extreme right can be seen as a reaction against the emergence of cartel parties and cartel party systems. The purpose of this paper is to refine this causal argument in the light of the three versions of the cartel party hypothesis identified in the literature. Statistical analyses are performed to compare and contrast the explanatory power of the three versions of the cartel party hypothesis. The analysis of the German and the Dutch data shows that the subjective version of the cartel party hypothesis has a greater explanatory power than the systemic and the systemic-subjective versions.